The Relationship of Knowledge and Attitude with Early Warning Score Practice in Nursing Profession Students - Megawati, Sri Wulan; Sumbara; Imam, Haerul (Corespub, 2025)
EWS is an early warning system that uses scoring to assess the deterioration of a patient's condition in the hospital. Nurses and students, as the implementers of nursing care, must develop their ability to understand EWS because it supports patient safety. Students' knowledge and attitudes in identifying patient deterioration can influence EWS practice, so it is necessary to explore how students' knowledge and attitudes relate to EWS practice, which is the focus of this study. The purpose of this study is to analyze the correlation between knowledge and attitudes and EWS practices. The research design is quantitative with a correlational approach. Sampling was conducted using a purposive sampling technique, where the sample consisted of 53 students who had completed emergency and critical care rotations. The research instruments consist of a demographic data questionnaire, an EWS Knowledge questionnaire, an EWS Attitude questionnaire, and an EWS Documentation Checklist. Data collection was carried out by distributing a link to complete the questionnaire thru g-form. Data analysis was performed using the Spearman and chi-square statistical tests. The research results show that the majority of respondents (52.83%) have good knowledge, the majority of respondents (71.70%) show a positive attitude, and the majority of respondents (64.15%) demonstrate appropriate practices in filling out the EWS. There is a relationship between knowledge and practice with a p-value of 0.006, and there is no relationship between attitude and EWS practice. The Sig. (2-tailed) value is 0.330.